Pola Komunikasi Pengasuh Dalam Membina Akhlak Santri di Pondok Pesantren Musthafawiyah Desa Purba Baru Kabupaten Mandailing Natal - Lubis, Alfan Mansyur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The New Musthafawiyah Islamic Boarding School is one of the private institutions that has an important role in developing the talents of the students at the pesantren in the learning process and various kinds of extracurriculars, be it general subjects, special subjects such as Islamic Religious education, Aqidah Akhlak, Fiqh and Al-Qur'an and Hadith. However, the author only focuses on the communication patterns used by the teacher or ustadz of the Old Musthafawiyah Islamic Boarding School in fostering the morals of students, where there are still some obstacles experienced by caregivers in fostering the morals of the students, namely that there are still many students who do not know the importance of character, behavior, character, temperament, character, behavior and good habits. Therefore, better communication patterns are needed to uphold the discipline of students. The type of research used in this research is a type of research with a descriptive qualitative approach, the data collection methods used are observation, interviews, and documentation. The results of the study can be concluded that the types of communication patterns that occur in the musthafawiyah Islamic boarding school are divided into three communication patterns, namely the wheel communication pattern where there is already communication between the leadership and the teacher by making direct visits. communication patterns of two-way communication circles using the question and answer method, lectures, as well as socialization between teachers and students, and star or all-channel communication patterns that involve all channels, be it the leaders of the Islamic boarding school, teachers or students. Then the inhibiting factors such as limited time, community environment, gadgets and special places for coaching, and the supporting factors are active students, and the use of language that is easy to understand.